Quality of Caregiver Services and Quality of Life among Chronic Illness Undergoing Home Care in Katingan Districts, Central Kalimantan, Indonesia - Natawirarindry, Catherine; Guino-o, Theresa A. (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: The chronically ill person often gets late treatment because there is a lack of family preparation to deal with the chronic disease process, resulting in a heavy burden on the community, family, and quality of life of persons with chronic diseases in the Katingan District. Objective: The study aimed to examine a relationship between caregiver services and quality of life in a chronically ill person undergoing home care. Methods: The research method used is correlational design. Participants were randomly selected: 187 chronically ill persons receiving care at home in six subdistricts in Katingan District, Central Kalimantan. The participants in this study had at least been suffering from chronic illnesses for more than three months during their home treatment. Results: there is a significant relationship between caregiver services for chronically ill persons and the quality of life of chronic sick persons (r = 0.471 and p = 0.00). Recommendation: The finding of this study be utilized as a guideline to the policymakers, community health canter, health workers, nurses, educators, family, and researchers to determine areas to improve caregiver services, which could translate into a significant improvement in the quality of life chronically ill persons